2008
DOI: 10.1111/j.1600-0560.2007.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratoacanthoma occurring within the red dye of a tattoo

Abstract: Keratoacanthoma (KA) is a common keratinizing squamous cell neoplasm of unknown origin characterized by rapid growth and spontaneous involution. Trauma‐induced forms have been observed with various types of skin injury. To our knowledge, reports of KA arising at tattoo sites are scarce in the literature. A 41‐year‐old woman with no medical history presented for a rapidly growing nodule confined to the red part of a tattoo located on the scapula. Histology showed a keratin‐filled cuplike crater with an epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 20 publications
0
30
0
2
Order By: Relevance
“…Epidemiological studies have indicated that risk factors for KA include sun exposure, chemical carcinogens, viruses, cutaneous infection, and trauma. KA has been reported to occur in sites of previous cryotherapy, topical photodynamic and UV therapies, megavoltage radiotherapy, split skin graft donor, excisional surgery scars, and tattoos (Swaw et al 1990 Kluger et al 2008). Many of these procedures are considered to cause local stress that induces Hsp60 overexpression (Jalili et al 2004;Singh et al 2009;Henderson 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have indicated that risk factors for KA include sun exposure, chemical carcinogens, viruses, cutaneous infection, and trauma. KA has been reported to occur in sites of previous cryotherapy, topical photodynamic and UV therapies, megavoltage radiotherapy, split skin graft donor, excisional surgery scars, and tattoos (Swaw et al 1990 Kluger et al 2008). Many of these procedures are considered to cause local stress that induces Hsp60 overexpression (Jalili et al 2004;Singh et al 2009;Henderson 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Trauma, scars or cutaneous chronic inflammation have sometimes been found as underlying the development of BCCs [2, 3], SCCs [4] and KAs [21]. In the latter, trauma seems specifically to be a crucial triggering factor as most cases occurred within the first year after tattooing [14, 15, 18, 19]. Only in one case did KA occur 9 years after tattooing [17].…”
Section: Discussionmentioning
confidence: 99%
“…Tattooing is a traumatizing procedure characterized by the introduction of exogenous pigment in the dermis by puncturing the skin. Even though cases of malignancies such as melanoma [1,5,6,7], basal cell carcinomas (BCCs) [8,9,10,11,12], squamous cell carcinomas (SCCs) [13, 14] and keratoacanthomas (KAs) [14,15,16,17,18,19] have been reported for the past 40 years, it remains unclear what role tattoos play in their pathogenesis. We report here 2 new cases and wish to discuss the arguments and counter-arguments for such a potential relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Next to these inflammatory skin reactions we have to consider also the possibility of the development of cutaneous conditions such as pseudolymphomatous reactions [11] and pseudoepitheliomatous hyperplasia [12]. The evolution in neoplastic lymphoma [13, 14], squamous cell carcinoma, and Keratoacanthoma [15] is a rare outcome, since this neoplastic condition usually appears when they are fully evolved and not with “premalignant” condition. Despite that, it is mandatory to perform histological examination when we are in front of suspected papulonodular lesions arising from a tattoo.…”
Section: Introductionmentioning
confidence: 99%